An unprecedentedly simple method of synthesis of aryl azides and 3-hydroxytriazenes12. Issue 22 (12th October 2016) - Gribanov, Pavel S.; Topchiy, Maxim A.; Golenko, Yulia D.; Lichtenstein, Yana I.; Eshtukov, Artur V.; Terekhov, Vladimir E.; Asachenko, Andrey F.; Nechaev, Mikhail S.
Abstract : Fischer's approach towards the synthesis of aryl azides and triazinoles from diazonium salts and hydroxylammonium chloride (phenylhydraxylamine) was reinvestigated and optimized. Abstract : Fischer's approach towards the synthesis of aryl azides and triazinoles from diazonium salts and hydroxylammonium chloride (phenylhydraxylamine) was reinvestigated and optimized. The new methodology enables the preparation of aryl azides and triazinoles in high yields in water at room temperature. The procedure is very simple, robust, easily scalable, reproducible, and "green".